(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Economic policyrefers to the actions that governments take in the economic field.It covers the systems for setting interestrates and government budget as well as the labormarket, national ownership, and many other areas of governmentinterventions into the economy. Such policies are often influenced by international institutions like the International Monetary Fund or World Bankas well as politicalbeliefs and the consequent policies of parties New economic policy was announced in year 1991. In thispolicy liberalization, privatization and globalization were mainly emphasized.Before 1991, public sector had been assigned important role in the economicdevelopment. Private sector was subject to rigorous control. but it wasrealized that public sector was inefficient because of bureaucratization,red-tapism, over staffing, lack of initiative etc. net result of of all thiswas the acute economic crisis in India in the year 1991.foriegn exchangereserves were too depleted to finance our imports even for two weeks. Freshloan were not available and nonresident fund were being withdrawn. Since July1991, the govt. of India has taken many policy measures with the objective ofpulling the country out of economic crisis and accelerating the rate ofeconomic growth. Main among them are: (1) replacing controlled economic byliberal one, i.e. reducing control and promoting liberalization (ii)encouraging private sector (iii) promoting foreign direct investment (iv)introducing improved technology (v) encouraging modernization of agriculture(vi) introducing extensive changes in trade policy monetary policy and fiscalpolicy (vii) keeping fiscal deficit under control. All these policy measuresare collectively called NEW ECONOMIC POLICY.